2017
DOI: 10.1093/treephys/tpx059
|View full text |Cite
|
Sign up to set email alerts
|

Continuous excitation chlorophyll fluorescence parameters: a review for practitioners

Abstract: This review introduces, defines and critically reviews a number of chlorophyll fluorescence parameters with specific reference to those derived from continuous excitation chlorophyll fluorescence. A number of common issues and criticisms are addressed. The parameters fluorescence origin (F0) and the performance indices (PI) are discussed as examples. This review attempts to unify definitions for the wide range of parameters available for measuring plant vitality, facilitating their calculation and use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 40 publications
1
54
0
Order By: Relevance
“…Leaf OJIP transients were measured in 3 h dark-adapted seedlings at room temperature using a Handy Plant Efficiency Analyzer (Handy PEA, Hansatech Instruments Limited, Norfolk, UK). All fluorescence parameters were calculated according to Jiang et al [27] and Banks [28].…”
Section: Methodsmentioning
confidence: 99%
“…Leaf OJIP transients were measured in 3 h dark-adapted seedlings at room temperature using a Handy Plant Efficiency Analyzer (Handy PEA, Hansatech Instruments Limited, Norfolk, UK). All fluorescence parameters were calculated according to Jiang et al [27] and Banks [28].…”
Section: Methodsmentioning
confidence: 99%
“…Both chlorophyll fluorescence (ChlF) and reflectance spectroscopy (i.e., photochemical reflectance index, PRI) are noninvasive techniques andoften used in physiologicalstudies to investigate a plant s response to various abiotic and biotic stresses in controlled environments and in the field [3]. The measurements of ChlF and PRI are simple and reliable methods for estimating the photosynthetic rate [4,5]. However, previous research also found that ChlF parameters were affected by the amount of photosynthetic pigments [6].…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of variable (F V = F M − F 0 ) to maximal fluorescence (F M ) was calculated. F 0 at T0 was used during this study (Banks 2017). The sensitivity of Fv/Fm is known to vary in response to drought stress (Banks 2018), researchers should use caution relying on this parameter alone for drought trials particularly when stress is not severe.…”
Section: Chlorophyll Fluorescencementioning
confidence: 99%